2000
DOI: 10.1063/1.1289809
|View full text |Cite
|
Sign up to set email alerts
|

Theory of energy gain in a laser-amplifier based on a photon-branched chain reaction: Auto-wave amplification mode under the condition of input signal focusing

Abstract: Huge energy gain is detected theoretically in a pulsed chemical laser amplifier based on a photon-branched chain reaction initiating in a gaseous disperse medium composed of H2-F2-O2-He and Al particles by focused external infrared radiation. It is shown that this effect is observed due to the possibility of the ignition of the laser–chemical reaction into an initial small focal volume of an active medium. It then spreads out of this minimal volume spontaneously in the auto-wave regime without external power s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…duration of the input signal, τ in ,was selected so that the enclosed energy in the focal volume, V f ~ 10 -7 cm 3 , was enough for the evaporation of particles of aluminum, for the initiation of the PBCR and, in the end, for deriving the generation of the laser. Calculations 6,7 show that at a given intensity in the field at the focal point, the threshold value τ in for a master oscillator generating radiation is 250 ns for the selected composition of the active laser mixture containing dispersed Al particles.…”
Section: Diffractive Focusing Of An Input Signalmentioning
confidence: 99%
See 2 more Smart Citations
“…duration of the input signal, τ in ,was selected so that the enclosed energy in the focal volume, V f ~ 10 -7 cm 3 , was enough for the evaporation of particles of aluminum, for the initiation of the PBCR and, in the end, for deriving the generation of the laser. Calculations 6,7 show that at a given intensity in the field at the focal point, the threshold value τ in for a master oscillator generating radiation is 250 ns for the selected composition of the active laser mixture containing dispersed Al particles.…”
Section: Diffractive Focusing Of An Input Signalmentioning
confidence: 99%
“…[2][3][4][5][6][7][8] We have considered the case of a confocal telescopic cavity with spherical mirrors (Fig. 1).…”
Section: Wave Optics Of a Laser-amplifiermentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretical investigations [1][2][3][4][5][6][7][8][9] have been carried out for the problem of photon branching in a two-phase (consisting of a gas and disperse particles) chemically active media. It has been shown that the introduction of a certain concentration of ultradisperse particles into the active medium of a chemical laser based on a chain reaction, and further their (particles) evaporation by external infrared (IR) radiation, can result in the generation of coherent radiation of energy considerably higher than the energy of an initiating input pulse at same frequency.…”
Section: Introductionmentioning
confidence: 99%
“…We have developed a relatively simple HF laser kinetic model [1,2] which includes the most important physical-chemical kinetics features under the assumption of rotational-translational nonequilibrium, 2 Laser Chemistry making it possible to calculate the specific energy of the coherent radiation, the pulse duration, the effective chain length of the reaction between fluorine and hydrogen, and the chemical and engineering efficiencies of the laser. This model was supplemented with an electrodynamical model [2][3][4][5][6][7][8][9] of the pulsed laser based on a solution of the wave equation. The wave approach for the description of a pulsed chemical HF laser amplifier based on a PBCR in an unstable telescopic cavity enables the detection of interesting optical effects in an active two-phase medium of H 2 -F 2 -O 2 -He and Al particles and also of the new properties of the laser.…”
Section: Introductionmentioning
confidence: 99%